(untitled) (MASKAY, 2019)
Ecuador currently proposes a productive matrix based not only on oil extraction but also on exploiting some minerals. As the mining of copper is a sector with many needs to solve, one of them is the control of weight at the exit of the same. For this reason, the University National of Loja built a prototype of a scale laboratory for trituration copper. The mathematical model of the same one was identified, employing two methodologies for the identification, one based on CADCS (Computer Aided Designed and Control Systems) and the other in Ident (identification system) that owns the MATLAB® software, to optimize this process. Next, four algorithms were presented that allowed control of the crushing process in a simulation: PID and Smith Predictor. Then, the results of the most relevant parameters were presented in a table. Finally, the best algorithm of control selected was implemented with the help of Arduino.